Long-term optical brain imaging in live adult fruit flies - Cheng Huang (Nature Portfolio, 2018)
Time-lapse imaging studies of more than a day in the fly brain have been infeasible until now. Here the authors present a laser microsurgery approach to create a permanent window in the fly cuticle to enable time-lapse imaging of neural architecture and dynamics for up to 10–50 days.